A meta-analysis of the role of subpopulation analysis in the qualification and quantification of sperm sample quality, and the relationship with male fertility - Paul, Tristen Lee (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.